An experimental and modeling investigation of tensile creep resistance of a stable nanocrystalline alloy. (15th October 2020) - Kale, C.; Srinivasan, S.; Hornbuckle, B.C.; Koju, R.K.; Darling, K.; Mishin, Y.; Solanki, K.N.
Abstract: Nanocrystalline (NC) materials possess excellent room temperature properties, such as high strength, wear resistance, and toughness as compared to their coarse-grained counterparts. However, due to the excess free energy, NC microstructures are unstable at higher temperatures. Significant grain growth is observed already at moderately low temperatures, limiting the broader applicability of NC materials. Here, we present a design approach that leads to a significant improvement in the high temperature tensile creep resistance (up to 0.64 of the melting temperature) of a NC Cu-Ta alloy. The design approach involves alloying of pure elements to create a distribution of nanometer sized solute clusters within the grains and along the grain boundaries. We demonstrate that the addition of Ta nanoclusters inhibits the migration of grain boundaries at high temperatures and reduces the dislocation motion. This leads to a highly unusual tensile creep behavior, including the absence of any appreciable steady-state creep deformation normally observed in almost all materials. This design strategy can be readily scaled-up for bulk manufacturing of creep-resistant NC parts and transferred to other multicomponent systems such as Ni-based alloys. Graphical abstract: Image, graphical abstract